Factors Influencing Hypertension Incidence in Bangun Sari Village: A Cross-Sectional Study - Sianturi, Anggina Cucu Khetri; Suraya, Rani; Maimunah, Putri; Lubis, Adelia Mazidah; Auzi, Shopiah; Septian, Maulana Randi; Manik, Hubban Fathani (Jurnal Keperawatan Priority, 2025)
Hypertension is theoretically influenced by several risk factors. The first risk factors are those that cannot be changed such as age, gender, and genetics. Modifiable risk factors include education, knowledge, behavior, and attitude. This study aims to identify factors that contribute to hypertension in Bangun Sari Village, Datuk Tanah Datar Sub-district. This study used a quantitative approach with a cross-sectional analytic design. The study population consisted of all residents of Bangun Sari Village, with a total population of 4,099 people and 1,148 households. The sample was taken using a purposive sampling technique, with the Lameshow formula, resulting in 94 respondents. Data were collected through observation sheets. The results showed a statistically significant relationship between age, knowledge, behavior, attitude, and occupation with the incidence of hypertension (with a p-value of 0.001 for all variables except education). There was a statistically significant association between employment status and the incidence of hypertension (p-value = 0.002). However, no significant association was found between education level and the incidence of hypertension (p-value = 0.501). Therefore, there is a statistically significant relationship between age, knowledge, behavior, attitude, and occupation with the incidence of hypertension, but there is no significant relationship between education level with the incidence of hypertension in Bangun Sari Village.